An overview of acupuncture in stroke recovery: A narrative review - Ning Cao; Brian Nguyen; Stephani Li; Richa Lamba; Ryan Hafner; Sheng Li (The Journal of the International Society of Physical and Rehabilitation Medicine, 2020)
Acupuncture has been used in stroke recovery in Eastern countries from ancient times. Increased interests and attention have been paid to understand how this oriental practice works for stroke patients in Western medicine. In particular, the effort has been made to study whether adjunct use of acupuncture to standard rehabilitation treatment could potentially further improve recovery after stroke. Therefore, in this comprehensive review of most recent literature, we are able to summarize some convincing evidence on beneficial effect of adjunct acupuncture treatment on poststroke recovery in the domains, including dysphagia, poststroke pain syndrome, and spasticity. Furthermore, some limited emerging evidence in the areas of motor recovery, insomnia, cognitive impairment, and depression is reviewed as well. This comprehensive review intends to provide insights about the potential clinical application of acupuncture for stroke rehabilitation and its future research direction.